ANALYSIS OF THE INFLUENCE OF SUBJECTIVE NORMS AND CONSUMER ANIMOSITY ON THE DECISION TO BOYCOTT ISRAEL-AFFILIATED PRODUCTS WITH BRAND JUDGMENT AS A MODERATING VARIABLE: A STUDY ON WEST JAVA MUSLIM COMMUNITY - Pasha, Muhammad Rifki Rasyid; Sari, Diana (Journal of Business Studies and Management Review, 2024)
The crimes committed by Israel on an international scale have a global impact that directly influences how Muslim consumers view and evaluate products affiliated with Israel. The aim of the research is to analyze the influence of Subjective Norms and Consumer Animosity on the West Java Muslim community's decision to boycott Israel-affiliated products with Brand Judgment as a moderating variable. This research uses a quantitative approach and collects data through survey methods. The purpose of the selection method is to select 150 respondents based on the West Java Muslim community for research purposes. This research uses the Structural Equation Modeling method assisted by SmartPLS software for data processing. The results show that Subjective Norms have a positive and significant effect on Consumer Animosity, Subjective Norms and Consumer Animosity have a significant positive effect on the Boycott Decision, while Brand Judgment is able to moderate the relationship between Consumer Animosity negatively and significantly on the Boycott Decision.